Discovering the potential of S. clavuligerus for bioactive compound production: cross-talk between the chromosome and the pSCL4 megaplasmid. (December 2017) - Álvarez-Álvarez, Rubén; Martínez-Burgo, Yolanda; Rodríguez-García, Antonio; Liras, Paloma
Abstract Background Streptomyces clavuligerus ATCC 27064, the industrial producer of the β-lactamase inhibitor clavulanic acid, carries 49 putative secondary metabolite gene clusters. These secondary metabolite gene clusters are distributed between its linear chromosome and the 1.8 Mb-plasmid pSCL4, a rich reservoir of bioactive compound gene clusters. Results The transcriptome and metabolome ofS. clavuligerus ATCC 27064 and the pSCL4− derived strain, S. clavuligerus pSCL4−, were analysed. Construction of theS. clavuligerus pSCL4− strain resulted in the excision of a 303 kb stretch in the right arm of the chromosome and its translocation to pSCL4, producing a 2.1 Mb plasmid named pSCL4* . The absence of pSCL4* results in changes in the transcription level of genes encoding regulatory proteins or proteins with various functions. Lack of pSCL4* results in upregulation of three chromosomal gene clusters for secondary metabolites (SMC), SMC18, for holomycin and N-propionylholothin biosynthesis, SMC11b for tunicamycin biosynthesis (located between SMC10 and SMC11), and SMC5. The SMC10, SMC11 and SMC6 gene clusters were downregulated, resulting in lower production of clavulanic acid, cephamycin C and desferrioxamine E, respectively. Clusters SMC8, SMC12, SMC13 and SMC19 were also downregulated. Production levels of bioactive compounds, such as alkylresorcinol or thiol-derived compounds, were affected in the plasmid-less strain. Conclusions The excision and translocation to pSCL4 of 303 kb from the right arm of the chromosome confirms that the ends of the chromosome arms are regions of high instability and supports the hypothesis that pSCL4 might have been excised fromS. clavuligerus chromosomal right arm end. Cysteine and methionine metabolism inS. clavuligerus lacking pSCL4* may differ from that of the wild type strain, given the absence of sulfur metabolism genes located either in pSCL4 or at the right end of the chromosome, which led to levels of dithiolopyrrolones (holomycin, N-propionylholothin) and acetylhomocysteine thiolactone (citiolone) higher than those of the wild type strain.S. clavuligerus pSCL4− shows strong differences in its transcriptome and metabolome; however, the loss of 2.1 Mb DNA is dispensable in this strain.